A wedding quilt for Ella - Eicher, Jerry S. (Eugene, Or. : Harvest House Publishers, 2011)
When her family pressures her to marry the new bishop, Ella asks for six months to heal from the death of her former fianc, Aden. Meanwhile Aden's brother Daniel helps Ella build her dream house incorporated into Ella's wedding quilt.
Includes discussion questions (p. [284]).
Keywords: Amish -- Fiction; Love stories; Christian fiction